Numerical Simulation of Melting with Natural Convection Based on Lattice Boltzmann Method and Performed with CUDA Enabled GPU (Communications in Computational Physics, 2018)
A new solver is developed to numerically simulate the melting phase changewith natural convection. This solver was implemented on a single Nvidia GPU basedon the CUDA technology in order to simulate the melting phase change in a 2D rectangularenclosure. The Rayleigh number is of the order of magnitude of 108 and Prandltis 50. The hybrid thermal lattice Boltzmann method (HTLBM) is employed to simulatethe natural convection in the liquid phase, and the enthalpy formulation is usedto simulate the phase change aspect. The model is validated by experimental data andpublished analytic results. The simulation results manifest a strong convection in themelted phase and a different flow pattern from the reference results with low Rayleighnumber. In addition, the computational performance is estimated for single precisionarithmetic, and this solver yields 703.31MLUPS and 61.89GB/s device to device datathroughput on a Nvidia Tesla C2050 GPU.